Digital Transformation of Data-Driven School Management for Improving Education Quality in the Thousand Islands, Indonesia - Dede Latipah; Muhamad Alimudin; Dyah Prita Anggraini (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2026)
This study examines the digital transformation of data-driven school management and its contribution to improving education quality in the Thousand Islands, Indonesia. The research addresses three objectives: assessing the level of digital readiness among island-based schools, analyzing current data management and utilization practices, and developing a contextual model of digital, data-driven school governance suitable for geographically isolated regions. A mixed-method explanatory sequential design was employed. Quantitative data were collected from 78 school leaders and administrative staff across 24 public elementary and junior secondary schools using structured questionnaires. Qualitative data were obtained through semi-structured interviews, observations, and document analysis to enrich statistical findings. Descriptive statistics indicated moderate levels of digital infrastructure readiness and data utilization. Pearson correlation and multiple regression analyses revealed that digital infrastructure readiness, data-driven management practices, and leadership support significantly predicted perceived improvements in education quality, with data-driven practices emerging as the strongest predictor. Qualitative findings highlighted adaptive leadership strategies, emerging digital governance roles, and evolving organizational cultures that support evidence-based decision making despite infrastructural limitations. The study concludes that digital transformation enhances education quality not merely through technological adoption but through the institutionalization of systematic data use and leadership-driven governance reform. The findings offer theoretical contributions to digital governance scholarship and practical guidance for policymakers seeking to strengthen education management in remote island contexts.